2024
DOI: 10.1007/s11269-024-03882-0
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of RainWater Harvesting Systems in Europe – Current State of Art and Future Perspectives

Katarzyna Wartalska,
Martyna Grzegorzek,
Maciej Bełcik
et al.

Abstract: Water scarcity and climate change led to changes in water management, especially in urban areas. RainWater Harvesting (RWH) is a promising technique that allows the collection and reuse of rainwater, as well as protecting sewage systems from overload. This article reviews the current state of RWH in Europe, including advantages, implementation, potential efficiency, usage requirements, quality, and treatment processes. The main findings include the importance of RWH as a sustainable water management technique,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 145 publications
0
2
0
Order By: Relevance
“…The current state of the art and future perspectives for rainwater harvesting systems in Europe were presented in the paper by Wartalska et al [10], whereas Dalman et al [11] and Jin et al [12] showed the costs and benefits of this subject. On the other hand, de Sá Silva et al [13] presented a review of the environmental, economic, and social aspects of the use of the rainwater harvesting systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current state of the art and future perspectives for rainwater harvesting systems in Europe were presented in the paper by Wartalska et al [10], whereas Dalman et al [11] and Jin et al [12] showed the costs and benefits of this subject. On the other hand, de Sá Silva et al [13] presented a review of the environmental, economic, and social aspects of the use of the rainwater harvesting systems.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of rainwater collection systems have been discussed in detail by Morey et al [24], Yawalkar et al [25], and Ertop et al [26]. Those authors have noted that rainwater can be utilised (1) as an additional source of water where demand is high but water from other sources is scarce, (2) to protect water resources, (3) to reduce the consumption of surface and groundwater resources, (4) to produce safe drinking water in the process of purification, (5) for watering plants and landscaping, and (6) to reduce unproductive outflow of water through rivers into the seas and oceans; at the same time, rainwater utilisation systems are (6) simple, easy to maintain, and cheap to operate, (8) can be used anywhere, regardless of the terrain, geology, or land development pattern, (9) can be used on-site in households or public utility facilities, (10) can improve the water management system, and (11) can protect urban areas from flooding and reduce the severity of floods during heavy rainfall. It has also been demonstrated that excess rainwater can be diverted and captured for groundwater recharge.…”
Section: Introductionmentioning
confidence: 99%